Nitrogen enrichment drives accelerative effect of soil heterogeneity on the flowering phenology of a dominant grass - Anna G. Krause; Ashley A. Wojciechowski; Sara G. Baer (Ecosphere)
Abstract Plant phenology is affected by both abiotic conditions (i.e., temperature, nitrogen enrichment, and drought) and biotic conditions (i.e., species diversity). The degree of spatial heterogeneity in soil resources is known to influence community assembly and dynamics, but the relationship between resource heterogeneity and phenology or the potentially interactive effects of soil resources on phenology are less understood. We leveraged a tallgrass prairie restoration experiment that has manipulated soil nitrogen availability and soil depth over 20 years to test the effects of environmental heterogeneity, nutrient enrichment, and potentially interactive effects of global change drivers (nutrient enrichment and a drought manipulation) on the phenology of a highly dominant prairie grass (Andropogon gerardii). We recorded the timing of major developmental stages of A. gerardii in plots containing four soil heterogeneity treatments (control, soil depth heterogeneity, nutrient/depth heterogeneity, and nutrient/precipitation heterogeneity). We found that the boot, first spikelet, and emerged spikelet stages of A. gerardii occurred earlier in treatments with greater heterogeneity of soil nitrogen, and this effect was driven by the accelerative effect of nitrogen enrichment on phenology. Reduced precipitation increased the flowering length of A. gerardii but did not otherwise affect developmental phenology. There were no interactive effects among any soil resource treatments on phenology. These results advance our understanding of the relationship between plant phenology and global change drivers, which is important for understanding and predicting the timing of plant resource use and the provision of resources to higher trophic levels by plants under varying levels of resource availability.